Energetic analysis on C3MR process for liquefaction on natural gas using open source software - Muhammad Luqman Mohd Idris (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The scope of this research will focus only for LNG due to its high complexity. C3MR process is chosen as a main topic in this paper. This is due to the previous success in similar process from [2,7]. Lastly, DWSIM is used as a tool to do the simulation and analysis for the C3MR process. As such a different platform (DWSIM) has been used to see how it performs.